On Occasion of the Public Defence of the Dissertation: Ethics of Dizziness: On the Relationship between Subjectivity and Inter-subjectivity in Kierkegaard’s Authorship, illuminated from the Perspective of dialogical Philosophy - Søltoft, Pia (KIERKEGAARDIANA, 1999)
On Occasion of the Public Defence of the Dissertation: Ethics of Dizziness: On the Relationship between Subjectivity and Inter-subjectivity in Kierkegaard’s Authorship, illuminated from the Perspective of dialogical Philosophy